1997
DOI: 10.1093/infdis/175.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Full or Partial Seroreversion in Patients Infected by Hepatitis C Virus

Abstract: Cases of partial seroreversion have been reported in hemodialyzed or immunodepressed patients, but spontaneous clearance of viremia associated with a disappearance of specific antibodies or clearance while receiving therapy has not been precisely documented in immunocompetent hepatitis C virus (HCV)-infected persons. A longitudinal study of markers of HCV infection in a cohort of 178 multitransfused patients followed over an 8-year period was done to establish well-documented cases of partial or full serorever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 25 publications
1
55
2
Order By: Relevance
“…After viruses clear, specifi c antibodies may disappear and persist thus for several years, and could very rarely be found in low concentrations over many years. 27 In these cases, however, HCV RNA is found in PBMCs which we did not fi nd in our study contingent. 28 It is, however, not impossible to fi nd HCV RNA in the liver tissue.…”
Section: Resultscontrasting
confidence: 69%
“…After viruses clear, specifi c antibodies may disappear and persist thus for several years, and could very rarely be found in low concentrations over many years. 27 In these cases, however, HCV RNA is found in PBMCs which we did not fi nd in our study contingent. 28 It is, however, not impossible to fi nd HCV RNA in the liver tissue.…”
Section: Resultscontrasting
confidence: 69%
“…16 A greater than 90% rate of clearance of HCV RNA in the liver of sustained virological response also indicates that a long-lived hepatic reservoir is unlikely to exist, [37][38][39] although another report detected hepatic HCV RNA in 50% of spontaneously aviremic seropositive subjects. 22 The slow decrease in anti-HCV antibody titers in subjects with spontaneously cleared viremia [40][41][42][43][44] as well as the complete seroreversion detected in 7% of transfusion-transmitted infections 5 may also reflect an absence of ongoing antigenic stimulation, indirectly supporting clearance of infection in persons who test HCV RNA-negative in plasma. Finally, our findings are supported by the lack of HCV transmission following 11 of 12 fresh whole blood transfusions (containing approximately 10 9 PBMC) from aviremic donors (using duplicate TMA).…”
Section: Discussionmentioning
confidence: 99%
“…Since GBV-C appears to be a common, nonpathogenic, persistent human virus, it could potentially serve as a gene therapy vector for lifelong expression of foreign genes in humans. In addition, recent data indicate that GBV-C viremia occurs in 35 to 40% of human immunodeficiency virus (HIV)-infected individuals (31,43), and two clinical reports suggest that GBV-C viremia delays clinical disease progression and mortality in HIV-infected people (26,44). Since we demonstrated that GBV-C replicates in CD4 ϩ T cells in vitro, it is tempting to speculate that GBV-C may cause viral interference with HIV, leading to delayed disease progression.…”
Section: Discussionmentioning
confidence: 99%